Changes in calls for police service with changes in routine activities and the arrival and passage of weather fronts - LeBeau, James L. (Journal of quantitative criminology, 1990)
Proceeding on the assumptions that the day of the week is the best predictor of the levels of calls for police service, that calls for police service emanate from the pursuit of routine activities, and that weather influences routine activities, this paper examines how the expected change in the level of calls for service for a particular day of the week in Chicago is altered with the arrival and passage of weather fronts. Fronts taking 1 day to pass Chicago have a broader effect on the changes in calls across the days of the week than fronts taking 2 days in passage. On the whole, the 2-day fronts significantly alter calls for service during the weekdays but not on the weekend, while 1-day fronts significantly alter calls on both weekdays and weekends. In general, cold fronts decrease calls for service, and warm fronts increase calls for service.